2023
DOI: 10.1002/fsn3.3377
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin and proanthocyanidin from Aronia melanocarpa (Michx.) Ell.: Purification, fractionation, and enzyme inhibition

Abstract: With the increase in people's income and living standard, consumers put forward higher requirements for the health, nutrition, safety, and function of food, resulting in the continuous growth of market demand for healthy food with biologically active compounds. It has received wide attention that berries with high content of bioactive substances such as different kinds of polyphenols (anthocyanins and proanthocyanidins), organic acid, and polysaccharides are associated with a lower risk of arteriosclerosis, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…Cultivation of plant cells is a promising branch of cellular agriculture with amazing potential in the large scale production of foods and technical goods [39,41,45]. The black chokeberry (Aronia melanocarpa) is a rich source of pigments (anthocyanins), polysaccharides and valuable antioxidants (flavonoids, phenolic acids and flavan-3-ol) [3,6,[11][12][13][14][15]58,59]. Because many of these secondary metabolites have proven health benefits, the Aronia was classified as a "superfood" [7,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultivation of plant cells is a promising branch of cellular agriculture with amazing potential in the large scale production of foods and technical goods [39,41,45]. The black chokeberry (Aronia melanocarpa) is a rich source of pigments (anthocyanins), polysaccharides and valuable antioxidants (flavonoids, phenolic acids and flavan-3-ol) [3,6,[11][12][13][14][15]58,59]. Because many of these secondary metabolites have proven health benefits, the Aronia was classified as a "superfood" [7,11].…”
Section: Discussionmentioning
confidence: 99%
“…The plant is popular, with fruits that are among the richest source of antioxidants and colorants among all berries [2][3][4][5][6][7]. Anthocyanins, procyanidins, flavonoids and phenolics, found in fruits, have severalbeneficial health properties such as antioxidant, anti-inflammatory, anti-cancerogenic, antidiabetic, cardioprotective and hepatoprotective effects [1,[8][9][10][11][12][13]. Aronia fruits also contain high amounts of dietary fibers and polysaccharides with interesting medicinal properties [1,4,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Further, C3R showed a considerable reduction in the cholesterol uptake in free cholesterol as well as mixed micelles in addition to the suppression of the NPC1L1 expression in Caco-2 cells [56]. Chen et al [70] found that C3G from Aronia melanocarpa exhibited the strongest inhibitory activity against α-amylase and lipase. However, cyanidin 3-galactoside, cyanidin-3-arabinoside, and cyanidin 3-xyloside did not show any effect on the α-amylase and lipase enzymes.…”
Section: In Vitro Studies On the Role Of C3g In Obesity-related Compl...mentioning
confidence: 99%
“…Aronia generally contains a higher proportion of anthocyanins than other fruits of the Rosaceae family [ 8 ], especially compared to strawberries, apples, or pears, which makes it even more prominent in its antioxidant capacity. In addition to anthocyanins, Aronia is rich in other polyphenolic compounds such as proanthocyanidins and flavonoids [ 9 ]. While these compounds are found in many fruits of the rose family, the content and variety are generally more abundant in Aronia.…”
Section: Introductionmentioning
confidence: 99%